Underreporting of Energy Intake and Bariatric Surgery - Ravelli, M. N. [UNESP]; Ramirez, Y. P.G. [UNESP]; Quesada, K.; Rasera, I.; de Oliveira, M. R.M. [UNESP] (My University, 2016)
Bariatric surgery changes food intake patterns, even for patients who are only on the waiting list. Because food intake is put in check, this can interfere in its reporting. Underreporting should be a consideration every time information is wanted on people undergoing bariatric surgery. The methods for assessing the plausibility of reported consumption are based on the comparison between true and estimated energy expenditure. Studies on nutritive patterns show that underreporting is not only quantitative, but also selective, occurring to a greater degree for food items that are more energy dense. The available methods consider body weight stability as an application criterion for surgery, excluding people who are losing or gaining weight; this is of great interest in the study of people undergoing bariatric surgery. The studies using stable isotopes and more complex statistical approaches can result in more accurate methods for this kind of evaluation.
Keywords: Energetic need; Energy consumption; Obesity; Stable isotopes; Underreporting of food intake